Biomedical Informatics Publications: a Global Perspective - Maojo, V.; Garcia-Remesal, M.; Bielza, C.; Crespo, J.; Perez-Rey, D.; Kulikowski, C. (Methods of Information in Medicine, 2012)
Background: In the past decade, Medical Informatics (MI) and Bioinformatics (BI) have converged towards a new discipline, called Biomedical Informatics (BMI) bridging informatics methods across the spectrum from genomic research to personalized medicine and global healthcare. This convergence still raises challenging research questions which are being addressed by researchers internationally, which in turn raises the question of how biomedical informatics publications reflect the contributions from around the world in documenting the research.Objectives: To analyse the worldwide participation of biomedical informatics researchers from professional groups and societies in the best-known scientific conferences in the field. The analysis is focused on their geographical affiliation, but also includes other features, such as the impact and recognition of the conferences.Methods: We manually collected data about authors of papers presented at three major MI conferences: Medinfo, MIE and the AMIA symposium. In addition, we collected data from a BI conference, ISMB, as a comparison. Finally, we analyzed the impact and recognition of these conferences within their scientific contexts.Results: Data indicate a predominance of local authors at the regional conferences (AMIA and MIE), whereas other conferences with a worldwide scope (Medinfo and ISMB) had broader participation. Our analysis shows that the influence of these conferences beyond the discipline remains somewhat limited.Conclusions: Our results suggest that for BMI to be recognized as a broad discipline, both in the geographical and scientific sense, it will need to extend the scope of collaborations and their interdisciplinary impacts worldwide.
Keywords: Biomedical informatics; medical informatics; bioinformatics; conference rankings; journal impact factor